Predictors of Well-Being in University Students: The Dominant Role of Social and Mental Balance and Physical Exercise over Dietary Habits and Daily Routines - Vršnik Perše, Tina; Grafenauer Ekart, Živa (Revija za elementarno izobraževanje, 2025)
This study examines the relationship between well-being, social and mental balance, physical exercise, dietary habits, and daily routines among university students. Using standardised questionnaires, we obtained results showing that social and mental balance is the strongest predictor of well-being, followed by organised physical exercise. Although dietary habits and daily routines are correlated with well-being, their predictive influence remains limited. The results point to the importance of holistic interventions that integrate social support, structured physical activity, and healthy lifestyle choices in increasing overall well-being. Future research should investigate longitudinal effects and intervention-based approaches to develop sustainable well-being strategies tailored to students' needs.
Keywords: university students, well-being, social and mental balance, physical exercise, dietary habits, daily routines.